1999
DOI: 10.1111/j.1600-079x.1999.tb00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation in humans of the effects of radiocellular telephones on the circadian patterns of melatonin secretion, a chronobiological rhythm marker

Abstract: A decrease in melatonin secretion has been observed in small mammals under exposure to extremely low frequency electromagnetic fields. As there is some concern about possible health effects of the increasing use of radiocellular telephones emitting radiofrequency electromagnetic fields, we examined whether such fields would alter melatonin levels in the human. Volunteers were two groups totalling 38 men, 20-32 yr old. Exposures were to commercially available cellular telephones of the GSM 900 type (Global Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 31 publications
(3 reference statements)
3
21
0
Order By: Relevance
“…So far there have been remarkably few researches carried out into the effects of RF GSM radiation on melatonin secretion. In human studies, no effects of GSM radiation were found either on salivary melatonin level [Radon et al, 2001] or on blood serum melatonin concentration [Mann et al, 1998;de Seze et al, 1999]. In laboratory animal studies, neither short [Vollrath et al, 1997] nor long term [Heikkinen et al, 1999] GSM RF exposure affected melatonin or 6SM production of rodents.…”
Section: Introductionmentioning
confidence: 95%
“…So far there have been remarkably few researches carried out into the effects of RF GSM radiation on melatonin secretion. In human studies, no effects of GSM radiation were found either on salivary melatonin level [Radon et al, 2001] or on blood serum melatonin concentration [Mann et al, 1998;de Seze et al, 1999]. In laboratory animal studies, neither short [Vollrath et al, 1997] nor long term [Heikkinen et al, 1999] GSM RF exposure affected melatonin or 6SM production of rodents.…”
Section: Introductionmentioning
confidence: 95%
“…A melatonin suppressing or a rebound effect has not been detected so far in randomized crossover trials of mobile phone exposure (radiation in the high frequency range, 900-1800 MHz) de Seze et al, 1999;Radon et al, 2001;Bortkiewicz et al, 2002]. Three of those studies investigated melatonin in the night following or during the exposure only Radon et al, 2001;Bortkiewicz et al, 2002].…”
Section: Discussionmentioning
confidence: 93%
“…Two recent observational studies have found evidence of an association between decreased excretion of melatonin during night and increasing use of mobile phones [Burch et al, 2002;Jarupat et al, 2003]. However, four cross-over trials have found no association between exposure to mobile phone handset and melatonin excretion de Seze et al, 1999;Radon et al, 2001;Bortkiewicz et al, 2002].…”
Section: Introductionmentioning
confidence: 98%
“…In primary pinealocyte cultures exposed in vitro to 60 Hz 0.05 mT vertical AC and 0.06 mT DC fields, melatonin production declined by almost 50% [Rosen et al, 1998], but in vivo studies of melatonin and other neurohormones revealed either increases [Lerchl et al, 1998;Zecca et al, 1998], decreases [Burch et al, 1999[Burch et al, , 2000Karasek et al, 1998;Reiter et al, 1998;Juutilainen et al, 2000], or no changes [Selmaoui et al, 1997;Truong and Yellon, 1997;Graham et al, 2000]. Pulsed microwave exposure at up to SAR 0.3 W/kg did not disrupt the normal circadian profile of melatonin or other hormones of the hypothalamo-pituitary-adrenal axis de Seze et al, 1998de Seze et al, , 1999, with the only exception of a commercial dairy herd kept in close proximity to a short wave (3-30 MHz) radio transmitter station. The animals in this herd, but not in another one, kept at a larger distance, exhibited a transient increase in salivary melatonin after the radio station was temporarily switched off [Stark et al, 1997].…”
Section: Effects On Neurohormonal Secretionmentioning
confidence: 97%